Contemporary Chinese Novels in Translation since 1978: Literary Voices from the Periphery - Wu, Yun (Routledge, 2025)
This book aims to complement the traditional focus of translation studies, which has primarily centered on translating English into other languages. It presents a comprehensive analysis of the reverse translation trajectory, exploring the movement of Chinese literature into the core English literary domain. The book aims to explore the ideological and sociological dynamics that underlie the translation of contemporary Chinese novels. This is achieved through an examination of the translation selection process, translation paratexts, and the roles of translation agents. Case studies are employed to illustrate specific linguistic, literary, and cultural challenges within translation. It dissects the cultural and literary implications of translating genres such as women's writing, science fiction, and Internet literature. The argument presented is that the translation of peripheral literature is indispensable in shaping global literature. Beyond its literary implications, the book identifies the political significance inherent in such reverse translation endeavors. It suggests that the translation of Chinese literature holds notable political interest for the Chinese government, which aims to reshape China's image and bolster the nation's soft power through literary translation. This work will be an essential read to students and scholars of translation studies, comparative literature, and Chinese studies.